World Agricultural Forum 2017 - Multilateral Negotiations on Agricultural Trade: State of Play - Rogerson, Evan (2017)
The World Agricultural Forum conference recently co-hosted by RSIS focused on three key themes – trade, food security and technology. Food security is a basic concern. Trade is an essential element in ensuring food supplies. Keeping the trading system open is a key priority. The WTO Ministerial in December 2017 is an important opportunity to reinforce the system.